Environmental Initiatives and Disclosures by Large companies: The Views of Investors - Salina Siddique; Nick Sciulli (Australasian Accounting, Business and Finance Journal, 2020)
The purpose of this paper is to explore investors' perspectives on the environmental initiatives and disclosure strategies of large firms. Obtaining such viewpoints is important because, as signaling theory suggests that investors' perspectives are one of the contributory factors in determining organisational strategies for environmental initiatives and disclosures. We used a web-based questionnaire of a group of investors. We put forward a hypothetical case study that raised financial versus environmental consequences of safe waste disposal initiatives for a large company. The findings revealed that a majority (90.21 per cent) of the investors preferred a pro-environmental strategy for waste disposal when a large firm in an environmentally sensitive sector is responsible for polluting the regional water resource. Our findings concluded that investors expect a high quality of environmental disclosures from larger firms as opposed to smaller firms. This study contributes to the literature by presenting investors perspective on firms' environmental decisions using a hypothetical case study.
Keywords: environmental initiatives; environmental disclosures; investors; dilemma